2011
DOI: 10.4065/mcp.2010.0820
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Management of Tuberculosis

Abstract: E ffective medical therapy for tuberculosis (TB) has existed for more than half a century, yet TB remains among the most pressing public health issues of our day. Tuberculosis is, in part, a disease of poverty. 1 The fact that it remains the eighth leading cause of death in the world speaks to the challenges facing practitioners and public health officials as they try to control a disease that is so entwined in the cultural and economic fabric of society. Challenges to effective solutions include lack of acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
114
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 85 publications
0
114
0
Order By: Relevance
“…The time required to treat TB can range from 6-9 months. This time duration not only increases the risk of a patient infecting more individuals but also increases the risk of the patient developing drug-induced hepatic damage (Sia and Wieland, 2011). Secondly, during tuberculosis infection, an imbalance between the T-helper cell 1 (Th1) and T-helper cell 2 (Th2) human immune responses exist, where it has been shown that an increase in the Th1 response could potentially be used as an immune therapy for active TB infections (Wong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The time required to treat TB can range from 6-9 months. This time duration not only increases the risk of a patient infecting more individuals but also increases the risk of the patient developing drug-induced hepatic damage (Sia and Wieland, 2011). Secondly, during tuberculosis infection, an imbalance between the T-helper cell 1 (Th1) and T-helper cell 2 (Th2) human immune responses exist, where it has been shown that an increase in the Th1 response could potentially be used as an immune therapy for active TB infections (Wong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…nations (WHO, 2015;Mesfin et al, 2015;Muvunyi et al, 2010;Nwadike et al, 2013;Sia et al, 2011). Historically, the scourge of PTB declined in the late 70s especially in developed countries until the advent of HIV which significantly increased its global incidence and altered its presentation consequently posing major clinical and laboratory diagnostic challenges especially in the resource-constrained nations.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 22% of countries worldwide routinely perform cultures and DST, and only 48% of the 46 countries in the WHO Africa region have ever undertaken a drug-resistance survey [4,73]. Moreover, DST is often too expensive, especially in high-burden countries, and in many settings it is neglected because of the lack of SLD [73,74]. In general, treatment for MDR-TB can extend up to 2 years after microbiologic culture conversion and relies on more toxic, less efficacious second-or third-line agents, many of which are even more scarce than frontline drugs in affected areas [75].…”
Section: Mdr and Xdr-tb Management Issuesmentioning
confidence: 99%